Metabolic routes affecting rubber biosynthesis in Hevea brasiliensis latex - Chow, Keng-See (Oxford University Press, 2012)
The cytosolic mevalonate (MVA) pathway in Hevea brasiliensis latex is the conventionally accepted pathway which provides isopentenyl diphosphate (IPP) for cis-polyisoprene (rubber) biosynthesis. However, the plastidic 2-C-methyl-D-erythritol 4-phosphate (MEP) pathway may be an alternative source of IPP since its more recent discovery in plants. Quantitative RT-PCR (qRT-PCR) expression profiles of genes from both pathways in latex showed that subcellular compartmentalization of IPP for cis-polyisoprene synthesis is related to the degree of plastidic carotenoid synthesis. From this, the occurrence of two schemes of IPP partitioning and utilization within one species is proposed whereby the supply of IPP for cis-polyisoprene from the MEP pathway is related to carotenoid production in latex. Subsequently, a set of latex unique gene transcripts was sequenced and assembled and they were then mapped to IPP-requiring pathways. Up to eight such pathways, including cis-polyisoprene biosynthesis, were identified. Our findings on pre- and post-IPP metabolic routes form an important aspect of a pathway knowledge-driven approach to enhancing cis-polyisoprene biosynthesis in transgenic rubber trees.